Transformasi Agama dari Ideologi Ke Politik: Brigade Tholiban di Priangan Timur Jawa Barat Indonesia - Dadang Kuswana (STAI AL-FALAH CICALENGKA, 2020)
Radical groups, such as Barisan santri, FPI, Gerakan Peduli Umat (GPI), KAMPU (Koalisi Aksi masyarakat peduli Ummat) Forum Pataruman, Forum Laskar Tasikmalaya (FLT), and other Islamic organizations, put pressure on the government. This movement was strengthened by the political will of the regional leadership of Tasikmalaya Regency, as seen in the regulations he issued. This research was conducted by direct observation and literature study. The results of this study indicate that first, Islam is seen as an ideology, a faith that may influence behavior but provides little opportunity for independent action. Islam is more of a